PENGARUH DISKUSI VERBAL DALAM REVIEW KERTAS KERJA AUDIT, PENGALAMAN KERJA, DAN MOTIVASI TERHADAP KINERJA AUDITOR PADA KANTOR BPK RI PERWAKILAN SULAWESI UTARA - Marunduh, Andrew P. (Universitas Sam Ratulangi, 2016)
Demands the implementation of public sector accountability towards the realization of good governance and claen governance in Indonesia is increasing. There are three main aspects that support the creation of good governance, namely monitoring, control and inspection. CPC was tasked to inspect / audit and give opinion on the financial statements prepared by the government. The purpose of this research is to know about the effect of verbal discussion in the review of audit working papers, work experience, and motivation on the performance of auditors in BPK RI Representative Office of North Sulawesi. Objects that are examined in this study is the Office of BPK RI Representative of North Sulawesi with a total population of 65 Auditor taken by census method. The independent variables used in this study is the verbal discussion (X1), work experience (X2) and motivation (X3), and the dependent variable is the performance of auditors (Y). This study uses multiple regression analysis and primary data in the form of a questionnaire, while for hypothesis testing done partially. Based on the analysis results can be seen the results of F = 12.876 and F table with a confidence level of 95% which df 1 (4-1) and df 2 (65-4-1) is a significant result by 2.76 to 0.000. So it can be seen that F count> F table it can be concluded that Ho is rejected and Ha accepted. Furthermore, it can be seen in the significant 0,000 <0.05, it can be stated that Simultaneously, variable Verbal discussions, work experience and motivation significantly influence Auditor Performance. Results thitung for Verbal Discussion variable (X1) = 5777 and the significant table = 0.000 and 2.000. From these results it can be seen that thitung> ttable can be stated that Ho refused and Ha is received and the significant level of 0.000 <0.05 Thus Verbal Discussions Auditor significantly influence performance. Results thitung to experience variable (X2) = 2.245 and 0.028, and significantly table = 2.000. From these results it can be seen that thitung> ttable can be stated that HO rejected and Ha is received and a significant level of 0.028 <0.05 Thus Work Experience Auditor significant effect on performance. Results thitung for motivation variable (X3) = 2,995 and 0,024 significant and table = 2.000. From these results it can be seen that thitung> ttable can be stated that HO rejected and Ha is received and a significant level of 0.028 <0.05 Thus a significant effect on performance motivation Auditor. Keywords: Verbal discussions, work experience, motivation, and Auditor Performance